2014
DOI: 10.2341/13-004-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of No-Ferrule and No-Post Buildup Design on the Fatigue Resistance of Endodontically Treated Molars Restored With Resin Nanoceramic CAD/CAM Crowns

Abstract: There was no influence of the buildup design on the performance of endodontically treated molars restored with RNC CAD/CAM complete crowns placed with self-adhesive cement. All restoration designs survived the normal range of masticatory forces. Failure mode tended to be more favorable with the 2-mm buildup or no buildup (endocrown).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
71
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 19 publications
6
71
0
10
Order By: Relevance
“…Concerns regarding such a procedure include the risk of root perforation and the need for removal of sound tissue in the root canal to facilitate the room for the post material, thus weakening the tooth-root complex. Moreover, the benefit of a post in the root canal for the overall retention of the successive reconstruction in general is being questioned in recent years [16]. Clinical results from long-term studies up to 17 years with crowns cemented on composite core build-ups have failed to demonstrate the merits of a metal post on the tooth survival in the presence of adequate ferrule effect [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns regarding such a procedure include the risk of root perforation and the need for removal of sound tissue in the root canal to facilitate the room for the post material, thus weakening the tooth-root complex. Moreover, the benefit of a post in the root canal for the overall retention of the successive reconstruction in general is being questioned in recent years [16]. Clinical results from long-term studies up to 17 years with crowns cemented on composite core build-ups have failed to demonstrate the merits of a metal post on the tooth survival in the presence of adequate ferrule effect [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies even showed that periodontal ligament simulation could change the fracture strength results and failure modes in a positive way in that the ligament could serve as a shock absorber [28,29]. In previous studies while some did not fill the canal [30], others did fill the canals with endodontic filling materials [3,6,16]. Although filling the canal may be considered clinically more relevant, in this study, in order to find out the material strength and their adhesion to the tooth solely, this factor was not considered.…”
mentioning
confidence: 99%
“…5 Ayrıca pulpa odasından sağ-lanan makromekanik destek sonucunda restorasyonun retansiyonu ve stabilitesi olumlu etkilenirken, 14 post yuvasının hazırlığı sırasında oluşabilecek olası riskler önlenir. 2 Adeziv simantasyon sayesinde ise korunan zayıf diş dokularının mikromekanik bağlantı ile dayanı-mının arttırılmasının yanı sıra, çiğneme kuvvetleri sırasında oluşan streslerin pulpa odası tarafından karşılanarak pulpa duvarlarına dağıtılması sağlanır. 5,14 CAD/CAM sistemi ile ölçü alma, alçı model elde etme, artikülatöre alma ve alt yapı -üst yapı hazırlığı gibi laboratuvar aşamaları ortadan kaldırılır.…”
Section: Discussionunclassified
“…[9][10][11] Ayrıca post yuvasının hazırlanması için kök kanal dolgu maddesi boşaltılırken kökte perforasyon oluşma riski bulunmaktadır. 2 Adeziv diş hekimliğindeki gelişmeler ile birlikte, daha konservatif yaklaşıma sahip olan endokron restorasyonları post-kor sistemlerine alternatif olarak tanıtılmıştır. 12 Endokronlar, kor yapısı ve kron restorasyonunu bünyesinde birleştiren monoblok (tek parça) restorasyonlardır.…”
unclassified
See 1 more Smart Citation